Sheepskin effects and the relationship between earnings and education: Analyzing the evolution over time in Brazil - Anna Risi Vianna Crespo; Maurício Cortez Reis (Institute for Applied Economic Research (ipea), 2015)
This paper seeks to analyze trends in sheepskin effects and earnings-education relationship on the Brazilian labor market from 1982 to 2004. Using data from the Brazilian National Household Sample Survey (Pnad) are estimated earnings equations including linear years of schooling, and splines and discontinuous functions for completed degrees, as well as semi-parametric regressions. Empirical evidence reports a reduction in the sheepskin effects from 1982 to 2004, indicating that a diploma or degree completion in Brazil has been loosing its value over time. At the same time, the relationship between log earnings and education has become more convex. Similar trends are verified when the analysis is carried out separately by region.
Keywords: I20; J30; 330